(untitled) (American Journal of Islam and Society, 1994)
Islam and Economic Development is another intellectual contribution by M. Umer Chapra, a well-known Muslim social scientist and author of Toward a Just Monetary System and Islam and the Economic Challenge. He has been devoting time, energy, and experience to the cause of Islamization of knowledge, and this work, which shares much in theme, tone, and territory with his earlier works, reflects his deep commitment and dedication to a painstaking task. This thought-provoking book, which offers a global and integrative perspective of the phenomenon of development within the framework of an Islamic worldview, is divided into six chapters, preceded by the author’s preface and a foreword by Zafar Ishaq Ansari, and followed by notes and refelences, a bibliography, and an index. Chapter 1, “The Kind of Development,” initiates the discussion of the book’s general theme by presenting the issue of development in terms of goals and the strategies employed to realize those goals. The two basic goals-efficiency and equity-are defined within the Islamic concept of just development, which is derived from the concepts of tawW (the oneness and unity of God), khikifah (the vicegerency of human beings), and ’adalah (justice) The terms “efficiency” and “equity,” as defined on page 8, need further explanation, especially when the authm has discussed the important analytical issue of the optimality and the maximization of the two variables. Moreover, the concept of khilafah (state) and the two basic goals that it seeks to achieve, ‘adalah (justice) and falah (general well-being), could have been better linked to the time basic pillars of Islam: tawhid, risalah (prophethood), and dkhirah (the hereafter). Chaptet 2, ”Can Secularism Foster Just Development?,” features development stmtegies of the two prominent secular systems: the free market system and the socialist system. Chapra points out that the reallocation of nsources cannot be realized within the value-neutral framework of secular systems. He notes that the ftee market system, which is based on the concept of self-intenst, cannot motivate people to act in the interest of society. He shows the futility of the Swirling pattern ...